Does Expanding Health Insurance beyond Formal-Sector Workers Encourage Informality? Measuring the Impact of Mexico’s Seguro Popular - Aterido, Reyes; Hallward-Driemeier, Mary; Pages, Carmen (2012)
Seguro Popular was introduced in 2002 to provide health insurance to the 50 million Mexicans without Social Security. This paper tests whether the program has had unintended consequences, distorting workers' incentives to operate in the informal sector. The analysis examines the impact of Seguro Popular on disaggregated labor market decisions, taking into account that program coverage depends not only on the individual's employment status, but also that of other household members. The identification strategy relies on the variation in Seguro Popular's rollout across municipalities and time, with the difference-in-difference estimation controlling for household fixed effects. The paper finds that Seguro Popular lowers formality by 0.4-0.7 percentage points, with adjustments largely occurring within a few years of the program's introduction. Rather than encouraging exit from the formal sector, Seguro Popular is associated with a 3.1 percentage point reduction (a 20 percent decline) in the inflow of workers into formality. Income effects are also apparent, with significantly decreased flows out of unemployment and lower labor force participation. The impact is larger for those with less education, in larger households, and with someone else in the household guaranteeing Social Security coverage. However, workers pay for part of these benefits with lower wages in the informal sector.